2020
DOI: 10.1002/anie.202003631
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Probe for Dehydrobutyrine

Abstract: Supporting information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Second-order rate constants of selected phosphine reactions with CpO 78. mode of reactivity could enable additional probe attachments or target enrichment. 323,324 The CpO-phosphine reaction is compatible with and orthogonal to several common bioorthogonal transformations. Mutually orthogonal reactions are desirable for simultaneous biomolecule tagging or activation.…”
Section: Cyclopropenone-phosphine Reactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second-order rate constants of selected phosphine reactions with CpO 78. mode of reactivity could enable additional probe attachments or target enrichment. 323,324 The CpO-phosphine reaction is compatible with and orthogonal to several common bioorthogonal transformations. Mutually orthogonal reactions are desirable for simultaneous biomolecule tagging or activation.…”
Section: Cyclopropenone-phosphine Reactionsmentioning
confidence: 99%
“…350−352 The phospha-Michael addition has enabled chemical retrieval of α,β-unsaturated carbonyl modifications and numerous profiling experiments. 323 Electron-deficient alkenes are relatively rare elsewhere in the cell. Thus, biomolecule targets purposefully outfitted with α,βunsaturated carbonyl groups can be selectively ligated with detectable probes via phospha-Michael addition.…”
Section: Phospha-michael Additionmentioning
confidence: 99%
See 2 more Smart Citations
“…1c ) was developed recently to label Dha and Dhb on proteins that were resistant to Michael addition chemistry using reagents containing thiol and amine nucleophiles. 12 Importantly, the probe engaged Dhb-containing proteins such as the MAPK ERK1/2 in cell lysate formed by the action of OspF and showed that the histone H3 is also a target of phospholyase activity. In the future, an unbiased mass spectrometry (MS) proteomic analysis of streptavidin-enriched peptides using the biotinylated probe may reveal additional novel dehydroamino acids in proteins.…”
Section: Dehydroamino Acids In Naturementioning
confidence: 99%